Hubungan Teori Fraud Hexagon Sebagai Pendeteksi Kecurangan Laporan Keuangan Pada Perusahaan Kelapa Sawit Yang Terdaftar di BEI - Tefanny; Wawan Andang Saputra (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
Financial statement fraud remains a critical issue in the business world, particularly within the palm oil plantation sector listed on the Indonesia Stock Exchange (IDX). This study explores the role of the Fraud Hexagon framework in explaining the potential occurrence of financial statement fraud during the 2019–2023 period. The Fraud Hexagon emphasizes six key aspects: external pressure, ineffective monitoring, rationalization, director turnover, political connections, and CEO duality. The research employs a quantitative approach using logistic regression, with the Beneish M-Score model applied as a tool to detect possible financial manipulation. The sample consists of 17 companies observed over five years, resulting in 85 data points. Findings indicate that only rationalization, represented by total accruals to total assets (TATA), has a significant effect on financial statement fraud. In contrast, other variables such as leverage, independent commissioners, director turnover, political connections, and CEO duality do not show meaningful influence. These results highlight that earnings management through accruals serves as a crucial indicator in detecting fraudulent behavior, particularly within the Indonesian palm oil plantation industry throughout the study period.